(1631) Evaluating the lightweight Currency System using the probabilistic Checking PRISM تقييم نظام العملة الخفيف باستخدام برنامج التحقق الاحتمالي PRISM - Helmi El Rayes, Amani (معهد التخطيط القومى, 2022)
Electronic commerce is one if the major factors in the evolution of the internet. It increases the possibility for private companies or individuals to trade with each other. Information plays a major role in such global economy. Immediate supply of information means improvement of the hole economy. The usual payment methods tend to be more unrealistic in such kind of commerce (information supply). Another kind of currencies is crated to help in this point. They are called alternative currencies.